Influence of hypovolemic and hypertonic treatments on plasma vasopressin levels and fluid balance in the propylthiouracil-induced hypothyroid rat - Mogulkoç, Rasim; Baltaci, Abdülkerim K.; Yilmaz, Bayram; Kelestimur, Haluk (Maghira and Maas Publications, 1999)
This study was undertaken to investigate the effects of hypovolemic and hypertonic treatments on plasma vasopressin (AVP) levels and fluid balance in propylthiouracil (PTU)-induced hypothyroidism in the rat. The influence of hypothyroidism on AVP responsiveness to hypertonic and hypovolemic stimuli were compared. Adult male rats were divided into two groups. Groups I and II were intraperitoneally (i.p.) injected with saline (1 ml/250 g) and PTU (10 mg/kg/day), respectively, for a period of two weeks. These groups were further divided in three subgroups each containing six rats. The first subgroup consisted of unchallenged rats. I.P 700 mg polyethylene glycol was used for hypovolemic treatment. The third subgroup consisted of hypertonic (1.5 M NaCl; 1 ml/100 g) stimulated animals. All rats were decapitated and trunk blood collected in heparinized tubes. Plasma samples were stored at -20°C until assayed. Plasma AVP, T3 and T4 levels were measured by radioimmunassay. Hematocrit values and plasma Na concentrations were also determined. In the PTU-induced hypothyroid rats, hypertonic treatment caused lower increase in plasma AVP levels (p < 0.05) compared to the respective control animals. In the hypovolemic group, decreases in AVP responses were not found to be statistically significant. In conclusion, although hypothyroidism does not statistically change basal AVP levels, it may affect AVP response to hypertonic stimulus. It is not clear whether changes in fluid-electrolyte balance cause disturbance in AVP release in hypothyroidism or vice versa. Therefore, these preliminary findings need to be confirmed by further investigations.
Keywords: Fluid balance; Hypothyroidism; Propylthiouracil; Rat; Vasopressin